Magnesium Recovery of Struvite Formation Based on Waste Salts (Bittern) with a Bulkhead Reactor - Luluk edahwati; Sutiyono; Nikmatuz Zahra; Herdiana Septiani (Engineering Faculty, University of Pembangunan Nasional Jawa Timur, 2020)
Waste salt or bittern is the residual liquid from the salt formation which cannot be precipitated again but can be obtained from the washing water remaining in the purification process. Bittern has high economic value of mineral salts such as MgCl2, MgSO4, KCl, and Br2. The element Mg in bittern can be used as a mineral forming struvite because magnesium is one of the components needed in the formation of struvite. Crystallization of the formation of struvite minerals occurs in equimolecular concentrations of Mg 2+, NH4 + and PO43 - in an alkaline state. The column reactor is equipped with a bulkhead which functions as a stirrer inside the reactor and is assisted by incoming air. Struvite solution (MAP) reacted can be formed from phosphoric acid, ammonium hydroxide, and bittern or salt waste as a source of magnesium with a molar ratio of 2: 1: 1. The pH variations run in the range of 7 to 11 and the reactor inlet air velocity between 0.25-1.25 L/min in a closed column reactor that is operated continuously. The resulting dry sludge was analyzed by XRD method for mineral characterization, SEM to determine the morphology of the crystals and XRF to determine the composition of struvite mineral.